2017
DOI: 10.1002/nau.23463
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and complications of adjustable continence therapy (ProACT™) after radical prostatectomy: 10 years’ experience in 143 patients

Abstract: Aims: To evaluate our outcomes of the adjustable continence balloons ProACT™ for the treatment of male stress urinary incontinence after radical prostatectomy. Methods: Between May 2007-August 2016 the ProACT™ was implanted in 143 patients without a history of radiotherapy. Endpoints were patient-reported changes in pad counts and complications. Treatment was considered successful if no pad or just one "security" pad per day sufficed, and improved if daily pad use was reduced by ≥50%. This is an open access ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
0
17
1
3
Order By: Relevance
“…29 Higher revision rates for ProACT were shown in papers with longer term follow up. Noordhoff et al 20 19,30 Patients still showed high satisfaction rates even after revisions, demonstrating that patient satisfaction is associated with continence achieved, not with the number of revisions. 31 For those individuals whose incontinence does not improve with ProACT therapy, this minimally invasive treatment can be easily reversed without hindering implantation of a more invasive therapy, such as AUS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…29 Higher revision rates for ProACT were shown in papers with longer term follow up. Noordhoff et al 20 19,30 Patients still showed high satisfaction rates even after revisions, demonstrating that patient satisfaction is associated with continence achieved, not with the number of revisions. 31 For those individuals whose incontinence does not improve with ProACT therapy, this minimally invasive treatment can be easily reversed without hindering implantation of a more invasive therapy, such as AUS.…”
Section: Discussionmentioning
confidence: 97%
“…Higher revision rates for ProACT were shown in papers with longer term follow up. Noordhoff et al had a 21.7% (31/143) revision rate at a median follow‐up of 56 months, Venturino et al had a 72.7% (16/22) revision rate at a median of 57 months, and Nestler et al had a 31% (41/134) revision rate at a median follow‐up of 118 months. Long‐term failures were primarily attributed to device leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The dry rate (45%) at last outpatient visit and reintervention rate (24%) found in the present study fall within the respective ranges. Additionally, the previously published results of adjustable continence balloons in patients with SUI postradical prostatectomy implanted by one of the surgeons of this study were added to Table to compare with the present study. Overall, results in the literature are slightly similar but important to note, besides the etiology, the size, and duration of follow‐up of study populations differ.…”
Section: Discussionmentioning
confidence: 99%
“…The latter device consists of two periurethrally placed balloons (ProACT TM ) whose volumes can be adjusted to achieve the optimal balance between voiding pressure and continence . Reported long‐term dry rates (no pad or one security pad) range from 45% to 66% with a follow up of 56 to 58 months . The majority or all patients included in these studies were treated for SUI after radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation